The Choice of Reforms and Economic System in the Baltic States. Issue 4 (December 2017) - Staehr, Karsten
Abstract This paper discusses the reforms that introduced market-based economies in the three Baltic states and seeks to identify particularities defining the resulting economic system. The reforms were rapid and broadly based and involved particular measures such as currency boards, free international trade, flat taxes and funded pension systems. The result was liberal-market economic systems with more emphasis on private enterprise, high-powered incentives and small governments than in most other post-communist countries. The unique choice of reforms may be seen as paradoxical given the proximity of the Baltic states to the Nordic welfare states. The choice may partly be explained by the initial economic and structural conditions of the countries, but the democratic and political dynamics as well as the preferences and values of the public are arguably of greater importance.